Role of Civil Society in SDG Localization: Reflections from Nepal - Sharma, Rajendra (NPRC Journal of Multidisciplinary Research, 2025)
This study aims to thoroughly examine the implementation of Sustainable Development Goals (SDGs) at both the global and national levels, shedding light on the process of SDG localization and the crucial role played by Civil Society in this endeavor. Drawing on a comprehensive range of reliable secondary sources from systematic review method, this research delves into the current status of SDG localization and offers valuable recommendations for its successful implementation. Furthermore, the study focuses on the challenges faced at the global and national levels in achieving the targets set by the SDGs for 2030. The findings of this research hold significant relevance for policymakers and researchers, providing them with valuable insights to inform their decision-making processes. SDG is a global term we need simply it in the local level, we have to rearrange the indicator and rewrite based on local government theorizing it from localization perspective. This paper concludes that the SDG localization in Nepal can promote ownership, participation, and targeted approaches, ultimately leading to more sustainable and inclusive development outcomes.